2020
DOI: 10.1371/journal.pone.0243038
|View full text |Cite
|
Sign up to set email alerts
|

HEK293 cell response to static magnetic fields via the radical pair mechanism may explain therapeutic effects of pulsed electromagnetic fields

Abstract: PEMF (Pulsed Electromagnetic Field) stimulation has been used for therapeutic purposes for over 50 years including in the treatment of memory loss, depression, alleviation of pain, bone and wound healing, and treatment of certain cancers. However, the underlying cellular mechanisms mediating these effects have remained poorly understood. In particular, because magnetic field pulses will induce electric currents in the stimulated tissue, it is unclear whether the observed effects are due to the magnetic or elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
(93 reference statements)
0
31
0
Order By: Relevance
“…Let us note that Pooam et al [18] reported that ROS production in HEK293 cells responds much more strongly to HMF than higher intensity static magnetic fields such as 500 µT . As it is evident from Fig.…”
Section: Results Of Our Calculations Favor Singlet-born [Fadh•••omentioning
confidence: 96%
“…Let us note that Pooam et al [18] reported that ROS production in HEK293 cells responds much more strongly to HMF than higher intensity static magnetic fields such as 500 µT . As it is evident from Fig.…”
Section: Results Of Our Calculations Favor Singlet-born [Fadh•••omentioning
confidence: 96%
“…Electron flow across plasma membrane proteins from intracellular electron donors (NADH) to the extracellular face is well documented (see 27 for review), though the exact mechanism remains obscure. There is also evidence of radical pair formation involving tryptophan radicals [28][29][30] in the absence of light. Such "dark"radical pair formation could excite the electron which then hops from one aromatic amino acid to another.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive exposure to PEMF, however, reduced ROS levels suggesting alterations in antioxidative stress response. Scavenging of radical species diminished the PEMF effect on osteoblast function [73]. Thus, it is concluded that PEMF elicited nontoxic amounts of ROS and that reactions to ROS generated by PEMF may also result in preconditioning for these cells [81].…”
Section: Primary Entities For Direct Coupling Emf To Cell: Cell Membrane (-+ De- Hyperpolarization) With Embedded or Coupled Molecules: Fmentioning
confidence: 92%
“…Changes in cellular ROS levels, induced by PEMF devices, may explain their beneficial and healing effects. Interestingly, concentrations of ROS induced by such devices are much lower than those induced by oxidative stress [72,73]. Paradoxically, ROS plays a beneficial role by stimulating antioxidant defense and repair pathways, and the therapeutic effects of PEMF have been documented in several pathologies involving defined cellular mechanisms [74].…”
Section: Primary Entities For Direct Coupling Emf To Cell: Cell Membrane (-+ De- Hyperpolarization) With Embedded or Coupled Molecules: Fmentioning
confidence: 99%